The Effect Of Digitalization On Culinary Msmes On Increasing Sales Turnover During Covid 19 Pandemic - Purnama, Suryari; Bangun, Cicilia S.; Panjaitan, Arop Ria S.; Sampoerna, Sulthan Taqi (Pandawan, 2022)
This study aims to determine the effect of digital marketing and the use of the marketplace for Culinary MSMEs on increasing sales turnover during the COVID-19 pandemic. The research population is Culinary MSMEs in DKI Jakarta whose number is unknown. Determination of the number of samples by Hair et.al (2014) which is a minimum of 50 culinary traders in Jakarta by sampling using the purposive sampling method, with the following criteria: Respondents are limited to small and micro entrepreneurs (UMK) Culinary, which sell heavy/main food, snacks (snacks) and various drinks, Culinary UMK actors who have used digital marketing as a promotional tool, Culinary UMK actors who have sold on marketplaces such as Gofood, Grabfood or Tokopedia. This research is a quantitative research that aims to see the effect of the data processing method used, namely Multiple Linear Regression Analysis. The results show: 1). There is an influence of digital marketing for Culinary MSMEs on increasing sales turnover during the covid 19 pandemic, 2). There is an effect of using marketplaces on increasing sales turnover of Culinary MSMEs, 3). There is an influence of digital marketing and the use of marketplaces on increasing Simultaneous sales turnover for Culinary SMEs. The novelty of this research is that it is found that the influence of the use of the marketplace is significant in increasing sales turnover, but specifically for Culinary MSMEs (Micro entrepreneurs) it turns out that the use of this marketplace reduces the sales turnover of these culinary Micro entrepreneurs.